Foraging Behaviour of Odontotermes wallonensis Wasmann - Shanbhag, Rashmi Ramesh; Sundararaj, R. (Indian Forester, 2014)
Contrary to the common perception that termites are indiscriminate eaters, termites choose their food carefully; however, the methods by which they choose food are not well understood. The movement of foragers of Odontotermes wallonensis, subterranean, mound building termite was investigated in their natural habitat using artificial feeding sites. Wooden blocks of different sizes were used to record foraging of termites and results revealed that for termites "size matters". Bigger the food source higher the preference. Termites selected larger sized baits over smaller one and also disturbance on the baits seems to have influence on the selection of food.